An Overview of the New Frontiers in the Treatment of Atherogenic Dyslipidemias. Issue 1 (11th April 2014) - Rached, F H; Chapman, M J; Kontush, A
<x xml:space="preserve">Abstract</x> Cardiovascular diseases (CVDs) are the leading cause of morbidity/mortality worldwide. Dyslipidemia is a major risk factor for premature atherosclerosis and CVD. Lowering low‐density‐lipoprotein cholesterol (LDL‐C) levels is well established as an intervention for the reduction of CVDs. Statins are the first‐line drugs for treatment of dyslipidemia, but they do not address all CVD risk. Development of novel therapies is ongoing and includes the following: (i) reduction of LDL‐C concentrations using antibodies to proprotein convertase subtilisin/kexin‐9, antisense oligonucleotide inhibitors of apolipoprotein B production, microsomal transfer protein (MTP) inhibitors, and acyl‐coenzyme A cholesterol acyl transferase inhibitors; (ii) reduction in levels of triglyceride‐rich lipoproteins with ω‐3 fatty acids, MTP inhibitors, and diacylglycerol acyl transferase‐1 inhibitors; and (iii) increase of high‐density‐lipoprotein (HDL) cholesterol levels, HDL particle numbers, and/or HDL functionality using cholesteryl ester transfer protein inhibitors, HDL‐derived agents, apolipoprotein AI mimetic peptides, and microRNAs. Large prospective outcome trials of several of these emerging therapies are under way, and thrilling progress in the field of lipid management is anticipated. Clinical Pharmacology & Therapeutics (2014); 96 1, 57–63. doi:10.1038/clpt.2014.85